(untitled) (Agriculture, Food, and Natural Resources Journal, 2024)
The research aimed to investigate the presence of Helminths on vegetables grown with confluence of untreated municipal and abattoir wastewater in the Kawo abattoir irrigation farm, Kaduna State, Nigeria. The wastewater sample was collected from four different points designated as WW01, WW02, WW03, and WW04. Vegetable samples were also collected from these points and labeled: SP01, SP02, SP03, and SP04 (spinach) and LT01, LT02, LT03, and LT04 (lettuce). The laboratory analysis of the samples was conducted using standard parasitological techniques, including macroscopy and microscopy, for Helminths in the wastewater and fresh vegetable produce. Ova of Fasciolopsis buski, Tania saginata, Cyst of Entamoeba histolytica and Ova of Ascaris lumbricoid were found and above the recommended guidelines, which specify <1 nematode egg per liter of wastewater. This study observed that untreated wastewater used for irrigation at the study site contains hazardous Helminths. This practice can be dangerous to consumers and life-threatening to farm workers due to physical contact with the wastewater. The study recommended the use of stabilization ponds (aerobic, facultative, and maturation) before using the water for irrigation, the adoption of safer irrigation methods such as drip or sub-surface irrigation to minimize contact of crops with contaminants present in irrigation water, and the use of personal protective equipment such as gloves, boots, trousers, and long sleeve shirts during farm work to reduce the level of exposure.